Предмет: Алгебра,
автор: fedorcukviktoria070
виконайте дії:
1)(4√3+3√2)(√27-√2)
Ответы
Автор ответа:
1
Ответ:
(4√3 + 3√2)(√27 - √2)
= 4√3(√27) - 4√3(√2) + 3√2(√27) - 3√2(√2)
= 4√(3 9) - 4√6 + 3√(2 9) - 3√2
= 4√9√3 - 4√6 + 3√2*3 - 3√2
= 4(3)√3 - 4√6 + 9√2 - 3√2
= 12√3 + 6√2
Отже, (4√3+3√2)(√27-√2) спрощується до 12√3 + 6√2.
друге не знаю
Объяснение:
fedorcukviktoria070:
дякую що зробив(ла) перше
Похожие вопросы
Предмет: Литература,
автор: molokovamargo2019
Предмет: Литература,
автор: golbankirill2
Предмет: История,
автор: shostakliza84
Предмет: Математика,
автор: dimabro753